Odpowiedz metaboliczna i hormonalna zawodnikow pilki recznej na standardowy wysilek treningowy - Opaszowski, B. H.; Krawczyk, A.; Obminski, Z.; Rojek, J. (Polish Journal of Sport and Tourism, 2010)
The aim of this study was to evaluate the metabolic and hormonal responses to the standard physical training of general development nature of the handball players differentiated by the players position on the field. Material and methods. The blood samples were examined for lactate concentration (LA) in whole blood, and cortisol (C), testosterone (T) and growth hormone (GH) in plasma before and after 1-hour training session. Results. It was found that the effort did not affect the concentration of C and T, whereas GH levels increased on average by 375%. Only in the case of the goalkeepers an increase in cortisol levels and the largest in comparison with other post-effort GH level were observed. In the case of the remaining players post-effort changes in concentrations of GH were significantly lower. Minor hormonal reactions of renal cortex and pituitary may be explained by better adaptation to the effort of active formations players (backcourt and pivot), as well as a relatively low intensity of the efforts carried out during the training session. Post-effort LA average level of 1.7 ± 0.39 mmol/L indicates a dominant share of aerobic processes in the metabolic workout energy security. Conclusions. The study revealed the usefulness of hormonal-metabolic indicators in monitoring to the physiological reaction of players undergoing a standard training session and its variation due to the position of a player on the field